Civil Society Responses to Changing Civic Spaces - Biekart, Kees; Kontinen, Tiina; Millstein, Marianne (EADI Global Development Series,, 2023)
This open access book contributes to thriving debates in academic as well as professional circles about the role of civil society in shrinking civic spaces, rising authoritarianism and right-wing populism, conflicts, fragile states, and most lately, the global COVID-19 pandemic. This is one of the first books to address the implications of changing civic spaces for civil society organizations worldwide. It offers a unique overview of how social movements and civil society groups in very different settings are responding to state-imposed restrictions of basic civic freedoms. The authors are all experts in the field, and their analyses are based on original and onsite research. This unique book also contributes to a better understanding of the conceptualizations and practices of civil society. It is of keen interest to academic scholars, students, civil society practitioners, and policy makers in the field of international development research and civil society action. Kees Biekart is Associate Professor at the International Institute of Social Studies (ISS) of Erasmus University (The Netherlands). He focuses on social movements, NGOs, civil society, civic-driven change, and participatory action research. Tiina Kontinen is Associate Professor in International Development Studies at the University of Jyväskylä (Finland), where she leads a research group on Citizenship and Civil Society in Development. She has published on civil society, NGOs, and North-South partnership and has led various projects with global research teams. Marianne Millstein is Senior Researcher at the Norwegian Institute of Urban and Regional Research (NIBR), Oslo Metropolitan University (Norway). She has published on urban politics, governance and planning, civil society, and citizenship. .